Membrane fouling by mixtures of oppositely charged particles - Lay, Huang Teik (2022)
Membrane fouling persists to be among key obstacles in liquid membrane-based separation processes, and thereby the underlying understanding has actively been pursued. The two gaps attempted to be addressed here are namely, (i) internal fouling, which has limited studies due to limitations of instruments available; and (ii) fouling by mixtures of oppositely charged particles, as an extension to the studies on effect of surface charge of pure foulants on fouling. With the sub-micron pure constituents (namely, negatively charged carboxylated latex particles and positively charged aminated latex particles) as benchmarks, mixtures of three different compositions of the two particle types were investigated. The membrane was polycarbonate track-etched (PCTE) membrane. Surprisingly, the mixtures gave worse flux decline than that by purely positively charged aminated latex, which contradicts electrostatic considerations. The fouling model indicates that the mixtures exhibited higher pore blockage parameters (α) than either of the pure constituents, which agree with the flux decline trends. On the other hand, the mixtures gave internal cake resistance parameters (Rc/Rm) in between that of the pure constituents, which disagree with the fouling trends. Furthermore, optical coherence tomography (OCT) analysis indicates that the mixtures had taller buildups on the membrane as well as heterogenous internal cakes. Therefore, the steepest flux declines for the mixtures seem to be better correlated with the extensive external fouling as manifested in the taller buildups on the membrane pores, rather than internal fouling since the internal cakes were more porous. The contradictory extensive external and mitigated internal fouling phenomena are unexpected based on electrostatic considerations, and thereby highlight that fouling resulting from mixtures may not be readily extrapolated from understanding based on pure particle feeds.